Dampak Presidensi G20 terhadap Perekonomian Indonesia Pasca Covid-19 - Putri Rifa Nurhidayah; Brigitta Andrea Trinita; Grace Kristin Malumma Tobing (Andalas Institute of International Studies, 2022)
This research aims to determine the economic growth after the entry and the Presidency of Indonesia in the G20. This study uses a qualitative type of research where we take sources from several journals, articles, and books related to the discussion. The theory that we use in this research is the theory of liberalism. Against the backdrop of the hustle and bustle of the Indonesian Presidency at this year's G20 and the efforts of G20 member countries in repairing and restoring the economy that had been knocked down due to the COVID pandemic that has attacked Hamoir 2 this year. Indonesia, which is also known as a bridge builder in the Asian region, makes Indonesia truly a role model and a bridge for recovery and new changes in the world economy of countries in both the Asian region and developing countries that are members of the G20.In this year's presidency, there are many new ideas launched by each country in developing and restoring its economy. Through the theme